Strategic planning of coal assets for electricity production: a case of Botswana. (29th June 2021) - Teseletso, Larona Sethunya; Adachi, Tsuyoshi
Ensuring affordable and sustainable energy access is core to Botswana's adapted Sustainable Development Goals (SDG 7). Presently, the country has deficient electricity supply whose local demand is expected to increase through to 2030. However, proven domestic coal resources would provide a cheap alternative source to enhance the electricity supply capacity. This study evaluates a potential coal mine, Sese mine, whose objective is to alleviate supply. It is valued using Real Options to determine its underlying project value. The investment model is leveraged from coal to electricity production by comparison of a prospective power plant location to minimise costs from producer to consumer. Scenario cost analysis of transportation systems is achieved to provide value to potential synergy for strategic planning. The findings show that the conveyor system has competitive cost advantage. Our study recognises the need for developing countries to utilise domestic resources to improve energy infrastructure to progress their economies.